2020
DOI: 10.1074/jbc.ra120.013589
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar localization of the yeast RNA exosome subunit Rrp44 hints at early pre-rRNA processing as its main function

Abstract: The RNA exosome is a multi-subunit protein complex involved in RNA surveillance of all classes of RNA, and is essential for pre-ribosomal RNA processing. The exosome is conserved throughout evolution, present in archaea and eukaryotes from yeast to humans, where it localizes to the nucleus and cytoplasm. The catalytically active subunit Rrp44/Dis3 of the exosome in budding yeast (Saccharomyces cerevisiae) is considered a protein present in these two subcellular compartments, and here we report that not only it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…5) but were more abundant in the rrp6Δ strain, suggesting that their levels are dependent on Rrp6 protein but not its exoribonuclease activity. While localization of exosomes might differ in the absence of Rrp6 protein, a recent study showed that depletion of Rrp6 did not alter nuclear transport or subcellular localization of Dis3 or other core exosome subunits (54). These results are also consistent with prior studies in which a catalytically inactive Rrp6 reduced the accumulation of poly(A) + RNAs when expressed in rrp6Δ yeast strains (55).…”
Section: Biochemistrysupporting
confidence: 87%
“…5) but were more abundant in the rrp6Δ strain, suggesting that their levels are dependent on Rrp6 protein but not its exoribonuclease activity. While localization of exosomes might differ in the absence of Rrp6 protein, a recent study showed that depletion of Rrp6 did not alter nuclear transport or subcellular localization of Dis3 or other core exosome subunits (54). These results are also consistent with prior studies in which a catalytically inactive Rrp6 reduced the accumulation of poly(A) + RNAs when expressed in rrp6Δ yeast strains (55).…”
Section: Biochemistrysupporting
confidence: 87%
“…The depletion of Srp1 or Kap95 levels in the cell leads to Rrp44 partial mislocalization, evidenced by a strong signal in the cytoplasm. Unlike Rrp6, the depletion of Sxm1 did not show any effect on Rrp44 localization 30 .…”
Section: Depletion Of Karyopherins Affect the Localization Of Exosome Subunitsmentioning
confidence: 68%
“…RNA exosomes play a pivotal role in processing and maturing rRNAs by trimming pre-rRNA intermediates and eliminating rRNA by-products [102][103][104]. In Arabidopsis, the loss of components of nuclear RNA exosome and cytoplasmic RNA decay processes triggers the production of aberrant rRNA-derived small RNAs [101,102].…”
Section: Aberrant Rrnas Serve As Sources Of Antisense Small Rnas That...mentioning
confidence: 99%